ANALYSIS OF THE DEVELOPMENT OF THE GAS INDUSTRY - T. Bobyleva; A. Khripunova (Вестник университета, 2016)
The article describes the current state, prospects of development of world and domestic gas industry. The analysis of exploration resources gas. Presented to world leaders in the production of natural gas. Describes the main trends affecting the development of the world gas market, special attention is paid to the active development of liquefied natural gas production. The different forecast scenarios of development of gas markets. Describes the basic scenario for gas demand, given attention to the problems of the gas industry and measures conducive to their achievement and future development of the gas industry.